PENERAPAN PRINSIP PENGAMANAN STANDAR SOP TERHADAP MANAJEMEN RESIKO PADA PT. MAYORA INDAH TBK - Titik Larasati; Edy Soesanto, Mochamad Gani Gynastiar, Afrizal Qimas Chairi (Adisam Publisher, 2024)
Companies are required to be able to carry out security systematically to support the implementation of production activities well and optimally. Security aspects need to be managed in an integrated manner through the implementation of a security management system. This research is important to use to apply principles that comply with SOP (Standard Operating Procedures) for risk management in companies. Therefore, researchers are interested in knowing the security design and the results of implementing security principles according to SOP (Standard Operational Procedure) standards for risk management at PT. Mayora Indah Tbk. The research object is PT Mayora Indah Tbk. The results of the research are implementing the security principles of the existing SOPs at PT Mayora Indah Tbk. consisting of the preventive principle, the principle of upholding goals, the principle of not taking risks, the principle of modification, the principle of vigilance and the principle of not interfering with freedom of movement as well as implementing a security implementation program in accordance with the risk management framework